Cognitive function and metabolic syndrome in unipolar and bipolar depression: A pilot study. (13th April 2021) - Jannini, T.; Longo, L.; Marasco, F.; Civita, M. Di; Niolu, C.; Siracusano, A.; Lorenzo, G. Di
Abstract : Introduction: Cognitive function is impaired in depressive disorders. Among several factors implicated in regulation of the cognitive function, metabolic syndrome has been showed have a pivotal role cognitive functioning in healthy controls. However, the role of metabolic syndrome in regulating the cognitive functioning of subjects affected by depressive disorders is little studied. Objectives: To investigate the effect of metabolic syndrome in regulation of cognition in unipolar and bipolar depression. Methods: One-hundred-sixty-five people affected by a depressive disorder (unipolar depression, UP; bipolar depression, BP) were enrolled at the Psychiatric and Clinic Psychology Unit of the University of Rome Tor Vergata, Rome, Italy. A group of healthy controls (HC) matched for agender and age was enrolled. The cognitive functions were evaluated with a computerized tool, THINC-it. Results: UP and BP had lower performances in THINC-it cognitive domains than HC. Metabolic syndrome is a negative, independent predictor of low performance in the THINC-it cognitive domains of people with depressive disorders. Conclusions: Our findings confirm that metabolic syndrome has a prominent role in determining the cognitive efficiency in depressive disorders, independently by the presence of a unipolar or bipolar depressive disorder. Metabolic syndrome has to be considered a major factor that should be considered in the treatment strategies of cognitive functioning improvement of people affected by depressive disorders. Disclosure: No significant relationships.